UNDERSTANDING ACCOUNTING INFORMATION, QUALITY, AND OPERATIONS SUSTAINABLE DEVELOPMENT PERFORMANCE: THE MEDIATING ROLE OF DIGITAL TRANSFORMATION - Lei Chen; Leong Mow Gooi; Fangnan Wei; Xuejing Song; Zhenguo Wang (Operational Research in Engineering Sciences: Theory and Applications, 2024)
An effective accounting information system allows for the seamless integration of modern digital tools into operational processes, leading to better decision-making and resource management for long-term success. The importance of decision sciences in utilising accounting data and digital technologies to promote sustainable development in organisational operations is highlighted. Therefore, the study sought to examine the comprehensibility of accounting information's influence on sustainable development performance by considering the mediating effect of digital transformation. Information was gathered by distributing a questionnaire to 384 executives from Chinese state-owned enterprises. The executives were selected using a convenient sampling technique. The study employed a quantitative research approach and utilised a cross-sectional research design. The findings of the PLS-SEM demonstrate that the quality of accounting information has a positive and significant impact on sustainable development performance and digital technology transformation. The digital transformation also has a noteworthy positive impact on sustainable development performance. Additionally, the study revealed that digital transformation plays a role in connecting the quality of understandable accounting information to sustainable development performance. This study contributes to the current body of knowledge by presenting a conceptual framework that examines the relationship between the clarity of accounting information, digital transformation, and corporate sustainable development performance. This study also assists enterprises in revaluating their sustainability strategies.